CO2 Emissions Embodied in International Migration from 1995 to 2015 - Liang, Sai; Yang, Xuechun; Qi, Jianchuan; Wang, Yutao; Xie, Wei; Muttarak, Raya; Guan, Dabo (Environmental science & technology, 2020)
While present international CO2 mitigation agreements account for the impact of population composition and structure on emissions, the impact of international migration is overlooked. This study quantifies the CO2 footprint of international immigrants and reveals their non-negligible impacts on global CO2 emissions. Results show that the CO2 footprint of international immigrants has increased from 1.8 gigatonnes (Gt) in 1995 to 2.9 Gt in 2015. In 2015, the U.S. had the largest total and per capita CO2 emissions caused by international immigrants. Oceania and the Middle East are highlighted for their large portions of immigrant-caused CO2 emissions in total CO2 emissions (around 20%). Changes in the population and structure of global migration have kept increasing global CO2 emissions during 1995-2015, while the reduction of CO2 emission intensity helped offset global CO2 emissions. The global CO2 mitigation targets must consider the effects of global migration. Moreover, demand-side measures need to focus on major immigrant influx nations.While present international CO2 mitigation agreements account for the impact of population composition and structure on emissions, the impact of international migration is overlooked. This study quantifies the CO2 footprint of international immigrants and reveals their non-negligible impacts on global CO2 emissions. Results show that the CO2 footprint of international immigrants has increased from 1.8 gigatonnes (Gt) in 1995 to 2.9 Gt in 2015. In 2015, the U.S. had the largest total and per capita CO2 emissions caused by international immigrants. Oceania and the Middle East are highlighted for their large portions of immigrant-caused CO2 emissions in total CO2 emissions (around 20%). Changes in the population and structure of global migration have kept increasing global CO2 emissions during 1995-2015, while the reduction of CO2 emission intensity helped offset global CO2 emissions. The global CO2 mitigation targets must consider the effects of global migration. Moreover, demand-side measures need to focus on major immigrant influx nations.